Impact of bariatric surgery on oral health conditions: 6-months cohort study - Moura-Grec, Patricia Garcia de; Yamashita, Joselene Martinelli; Marsicano, Juliane Avansini; Ceneviva, Reginaldo; Leite, Celso Vieira de Souza [UNESP]; Brito, Gilberto Borges de; Aparecido Brienze, Sergio Luis; Carvalho Sales-Peres, Silvia Helena de (Wiley-Blackwell, 2014)
Objectives: We evaluate oral health conditions before and after bariatric surgery. Methods: The sample was composed of 59 patients who had undergone Roux-en-Y gastric bypass (RYGB). Salivary flow, periodontal pocket depth and dental wear were evaluated before and after 6 months of surgery. Body mass index (BMI), C-reactive protein (CRP) and glucose levels were obtained from the patient's medical files. A t-test was used for dependent samples. Results: The mean BMI decreased from 49.31 +/- 8.76 to 35.52 +/- 8.12 kg/m(2) in 6 months after surgery (P < 0.000). Before surgery, 67% of patients had high levels of CRP and 38% higher blood glucose levels and after surgery there were significant reductions in these levels (P < 0.001). Salivary flow ranged from 0.84 to 0.95 ml/min. There was increased prevalence of periodontal pockets (P = 0.022) and mean pocket depth increased to about 0.5 mm (P < 0.001). The percentage of surfaces with dental wear in dentine was significantly higher after bariatric surgery (P = 0.002), while dental wear in enamel decreased (P = 0.019). Conclusions: Bariatric surgery may improve systemic conditions. However, it had a negative impact on oral health conditions because of an increase in periodontal disease and dental wear.
Keywords: Bariatric surgery; oral health; periodontal diseases; tooth erosion; obesity; salivary flow